Diaminocyclopentane - l-Lysine Adducts: Potent and selective inhibitors of human O-GlcNAcase - Weber, Patrick; Bojarová, Pavla; Brouzdová, Jitka; Křen, Vladimír; Kulik, Natalia; Stütz, Arnold E; Thonhofer, Martin; Wrodnigg, Tanja M (Bioorganic chemistry, 2024)
A new class of compounds, namely highly substituted diaminocyclopentane-l-lysine adducts, have been discovered as potent inhibitors of O-GlcNAcase, an enzyme crucial for protein de-O-glycosylation. These inhibitors exhibit exceptional selectivity and reversibility and are the first example of human O-GlcNAcase inhibitors that are structurally related to the transition state of the rate-limiting step with the "aglycon" still in bond-length proximity. The ease of their preparation, remarkable biological activities, stability, and non-toxicity make them promising candidates for the development of anti-tau-phosphorylation agents holding significant potential for the treatment of Alzheimer's disease.
Keywords: cyklopentany; Glycosidase; Lysine; lysin; vztah mezi dávkou a účinkem léčiva; Cyclopentanes; Molecular Structure; Enzyme Inhibitors; Structure-Activity Relationship; beta-N-Acetylhexosaminidases; lidé; molekulární struktura; Dose-Response Relationship, Drug; Hexosaminidase; Alzheimer’s disease; Tau protein; inhibitory enzymů; Diaminocyclopentane; Inhibition; vztahy mezi strukturou a aktivitou; beta-N-acetylhexosaminidasy; O-GlcNAcase; Humans